The effect on CO2 emissions of taxing truck distance in retail transports. (March 2017) - Carling, Kenneth; Håkansson, Johan; Meng, Xiangli; Rudholm, Niklas
Highlights: The environmental net effect of a partial tax on road transports is assed. The case is a Swedish regional retail market where the tax not yet is in place. We predict the net effect on CO2 emissions to be positive. The off-set of the net effect is some 50% because of a slower transition to e-tailing. Abstract: To finance transportation infrastructure and to address social and environmental negative externalities of road transports, several countries have recently introduced or consider a distance based tax on trucks. In competitive retail and transportation markets, such tax can be expected to lower the demand and thereby reduce CO2 emissions of road transports. However, as we show in this paper, such tax might also slow down the transition towards e-tailing. Considering that previous research indicates that a consumer switching from brick-and-mortar shopping to e-tailing reduces her CO2 emissions substantially, the direction and magnitude of the environmental net effect of the tax is unclear. In this paper, we assess the net effect in a Swedish regional retail market where the tax not yet is in place. We predict the net effect on CO2 emissions to be positive, but off-set by about 50% because of a slower transition to e-tailing.